Evaluasi Pembelajaran Mikro Mahasiswa Peminatan Mesin Produksi Pada Program Studi Pendidikan Teknik Mesin Universitas Sebelas Maret Menggunakan Model Cipp - Ramaditya Pandu Mulyono; Ranto Ranto (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
This study aims to determine the evaluation results of the implementation of the Microteaching course in the Production Engineering specialization of the Mechanical Engineering Education Study Program, Faculty of Teacher Training and Education, Universitas Sebelas Maret, based on the aspects of context, input, process, and product, as well as the overall evaluation results related to the implementation of the Microteaching course in the Production Engineering specialization of the Mechanical Engineering Education Study Program, Faculty of Teacher Training and Education, Universitas Sebelas Maret. This research is a summative evaluation research employing a concurrent mixed methods approach with descriptive analysis. The data were obtained through questionnaires and interviews. The results show that the Microteaching course is an important course and serves as a distinguishing course between teacher education programs and non-teacher education programs. The implementation of the Microteaching course in the Production Engineering specialization of the Mechanical Engineering Education Study Program, Faculty of Teacher Training and Education, Universitas Sebelas Maret indicates that the context aspect falls into the good category with an average score of 3.9. The input aspect is categorized as good with an average score of 3.7. The process aspect is categorized as good with an average score of 3.9. The product aspect is categorized as very good with an average score of 4.3. Overall, the implementation of the Microteaching course in the Production Engineering specialization obtained an average score of 3.9, which falls into the good category.